2020
DOI: 10.1021/acscatal.0c02771
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Redox Behavior of the [4Fe–4S] Subcluster in [FeFe] Hydrogenases

Abstract: [FeFe] hydrogenases are efficient catalysts for interconverting hydrogen with protons and electrons, whose catalytic mechanism remains a subject of controversy. Their active site, the H‑cluster, is composed of a [4Fe–4S] subcluster ([4Fe–4S]H) covalently attached to a [2Fe] subcluster ([2Fe]H). The two subclusters are strongly redox-coupled, and proton-coupled electron transfer (PCET) within the H-cluster is thought to be essential for catalytic activity. Additionally, proton-coupled reduction of [4Fe–4S]H has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 52 publications
1
32
1
Order By: Relevance
“…The counterintuitive formation of Hred at potentials lower or higher than HredH + , as a function of pH, is in marked contrast with previous studies on CrHydA1, 13 where they coexist at the same potentials, but it correlates extremely well with studies on DdH. 11,21 The fact that CpI features this behaviour is likely due to redox anti-cooperativity between the H-cluster and the proximal F-cluster (present in both CpI and DdH but absent in CrHydA1). Some of the IR signals discussed above have been proposed to be due to the incorporation of a degraded form of the synthetic precursor [2Fe] adt in DdH (namely 1988 and 1921 cm -1 ).…”
Section: Please Do Not Adjust Marginscontrasting
confidence: 80%
See 2 more Smart Citations
“…The counterintuitive formation of Hred at potentials lower or higher than HredH + , as a function of pH, is in marked contrast with previous studies on CrHydA1, 13 where they coexist at the same potentials, but it correlates extremely well with studies on DdH. 11,21 The fact that CpI features this behaviour is likely due to redox anti-cooperativity between the H-cluster and the proximal F-cluster (present in both CpI and DdH but absent in CrHydA1). Some of the IR signals discussed above have been proposed to be due to the incorporation of a degraded form of the synthetic precursor [2Fe] adt in DdH (namely 1988 and 1921 cm -1 ).…”
Section: Please Do Not Adjust Marginscontrasting
confidence: 80%
“…[17][18][19] A 1-electron reduction of the H-cluster in Hox yields the reduced state Hred that features a similar geometry with a [4Fe4S] 1+ -Fe(II)Fe(I) configuration. 13,20,21 An alternative nomenclature refers to this species as Hred'. 15,22 The protonated reduced state HredH + (Hred according to the alternative nomenclature) displays a [4Fe4S] 2+ -Fe(I)Fe(I) configuration and can be obtained either by a single proton binding to Hred (with simultaneous intra-cluster electron transfer from [4Fe4S] to Fe p ), or by proton-coupled electron transfer (PCET) from Hox.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, Rodríguez-Macia et al found the redox potential of the [4Fe-4S] cluster in CrHydA1 PDT to be independent from bulk pH. 48 The reasons for this discrepancy are unclear. In our hands, present and previous data 31,38 support PCET in the formation of Hred′.…”
Section: Discussionmentioning
confidence: 99%
“…24,47 The influence of bulk pH on Hox, Hred, and Hsred in the native [FeFe]-hydrogenase from Chlamydomonas reinhardtii (CrHydA1) 32,39 and Hred′ in cofactor variant CrHydA1 PDT was analysed before. 31,48 To understand the equilibrium of Hred′ and Hred in native CrHydA1, we now investigate the pH-dependent accumulation of both 1e − -reduced H-cluster states under turnover conditions. Making use of operando attenuated total reflection Fourier-transform infrared (ATR FTIR) spectroscopy and spectro-electrochemistry under H 2 oxidation or H 2 evolution conditions, we found consistent trends for an accumulation of Hred′ towards alkaline pH values whereas the accumulation of Hred increases towards acidic pH values.…”
mentioning
confidence: 99%